Membangun e-Loyality dan e-Satisfaction Melalui e-Service Quality Pengguna Goride Kota Semarang - Sri Suprapti; Suparmi Suparmi (Universitas Medan Area, 2020)
This study aims to analyze the direct and indirect effects of E-Service Quality on E-Loyalty, and the effect of E-Satisfaction o E-Loyalty on the use of Goride in the city of Semarang. The population in this study is GoRide users in the city of Semarang. The sampling method is accidental sampling and purposive sampling, with a total sample of 99 respondents. The data analysis technique use is path analyser. The results showed the E-Service Quality (X) variable had a positive and significant effect on E-Satisfaction (Z) and E-Loyalty (Y). The E-Satisfaction (Z) variable has an insignificant positive effect on E-Loyalty(Y) meaning that E-Service Quality(X) can directly influence E-Loyalty(Y), but cannot indirectly influence E-Loyalty(Y), so E-Satisfaction(Z) cannot mediate the effect of E-Service Quality(X) on E-Loyalty(Y).